Assessing Service Quality in Academic Libraries: User Perspective - Somaratna, Sajeewanie D. (VDM Verlag Dr. Müller, 2011)
In virtually any field of endeavour today access to information is a pre-requisite for success. Libraries form the repositories of information with user friendliness as their mission. There is, therefore a need for new ways to evaluate library performance. User satisfaction is an important measure of service quality in libraries. User perceptions about academic libraries seem to have been largely ignored by library management in developing countries. The assessment of service quality from the user perspective provides an important feedback for libraries to assess and improve their services. This book based on a research conducted at the University of Colombo is an attempt to assess the service quality of University libraries from the user perspectives. The book incorporates facts on the theories and applications of service quality models including SERVQUAL, factors affecting service quality, predictors of service quality and the analysis of service quality gaps. The author hopes that the book will help shed light on the important aspect of service quality in academic libraries and prove useful to Librarians, researchers and administrators in the higher education sector.
Keywords: Assessing Service Quality in Academic Libraries: User Perspective